University proceedings. Volga region. Social sciences - L.V. Rozhkova; O.V. Sal'nikova (Известия высших учебных заведений. Поволжский регион: Общественные науки)
Background. Russia today seeks to play significant role in the world order system, acting as major player in the international arena in processes of ensuring global security, stability and sustainability of international system. The purpose of the study is socio-logical analysis of youth perception of multipolar world ideas and international security architecture. Materials and methods. The study of young people’s assessments of international relations modern system and Russia's role in it is based on materials of the author's research in 2024, analysis of documents on foreign policy, international and national security of the Russian Federation. Results. Based on theoretical analysis and documents of the Russian Federation understanding of “multipolarity” concept is analyzed, models of international security are considered, perceptions of youth about transnational challenges, threats, as well as the role of Russia and international organizations in maintaining security and peace are investigated. Conclusions. Over the past few years, Russia has been actively promoting ideas of multipolar world, striving to form more sustainable system of international security and seeing its global role in this process. Youth believe that the key criteria for multipolarity are the sovereign equality of countries and cooperation with balance of interests. Stability in ensuring international security can provide counteraction to policy of double standards. However, according to youth's self-assessments, the UN has little influence in process of ensuring stability. Russia is a guarantor of peace and security.